Vulnerabilidades territoriais, pandemia e emprego: Uma análise exploratória de perfis socioeconómicos municipais e impactos da COVID-19 em Portugal - Ferrão, J.; Pinto, H.; Caldas, J. M.; Carmo, R. M. (Revista Portuguesa de Estudos Regionais, 2023)
The pandemic originated a set of impacts of different magnitudes in the territory. This article presents an exploratory approach to understand how the existence of certain vulnerabilities in the pre-crisis moment led to different impacts on territories in Portugal. Starting from the municipal scale, the analysis defines a typology of vulnerable territories according to the degrees of exposure and susceptibility they present, and compares the different groups of municipalities in this typology with territorial impacts of the pandemic crisis in terms of unemployment dynamics. The results attest to the existence of increased vulnerabilities in territories highly dependent on tourism and those that are part of metropolitan areas, whose socioeconomic structures resulted in situations of higher un-employment growth in 2020. The article has implications for reflection on territorial vulnerability, resilience and policies to transform the Portuguese economy in the post-pandemic period.